Exploring models of formation and dynamic evolution of satellites and rings of the solar system - Madeira, Gustavo Oliveira (2023)
Accretion in a circumstellar disk is the main mechanism for the formation of planets, while the formation of satellites and rings can occur through different mechanisms around the central body. This thesis aims to study the formation and stability of different systems of satellites and rings, in different environments and epochs of the Solar System. For this, we employ different numerical techniques. The topics addressed in the thesis are: the formation of Galilean satellites of Jupiter in a circumplanetary disk, the formation of Phobos of Mars due to a material recycling mechanism, the stability of 1+N co-orbital satellites confining the Neptune arcs and their formation due to the disruption of a satellite, and stability around spherical objects with a mass anomaly. We study the Galilean satellites using N-body numerical simulations and assuming that they formed in a circumplanetary disk during the last stages of Jupiter’s formation. The model assumes impacts between satellitesimals, pebble accretion, and includes gas-driven migration, gas tidal damping, and drag. Under these effects, satellites migrate inwards stopping their migration when reaching the disk’s inner cavity or when captured in mean motion resonances. In the system that best matches the masses of the real Galilean system, pairs of adjacent satellites are obtained in 2:1 mean motion resonances. We propose that the Galilean satellites system is a primordial resonant chain and that Callisto left the resonance without breaking the Laplacian resonance via divergent migration due to tidal interactions. The formation of Phobos was analyzed using 1D simulations of disk/satellite interactions. The model assumes that Phobos is a low-cohesion satellite formed through a cascade of disruptions and re-accretions of several parent bodies in a debris disk around Mars. We find that the recycling mechanism must, in fact, take place if the debris disk gives rise to low-cohesion objects. However, if Phobos were formed by this process, it would be accompanied today by a Roche-interior ring. So Phobos cannot be the outcome of such a recycling process. Turning attention to stability of rings, we study the equilibrium configurations for 1+N co-orbital satellites confining the Neptune rings. We use N-body simulations and obtain distinct configurations of satellites, with different numbers and sizes of moonlets, capable of confining arcs. Then, the formation of these possible co-orbital satellites is analyzed assuming the disruption of an ancient body at a Lagrangian point of a moon. The disruption fragments spread out and collide to form the co-orbital system. In such a scenario, the arcs likely formed through a mixture of different processes, with impacts between fragments and meteoroid impacts with the formed moonlets being attractive possibilities. Finally, we use the Poincaré surface of section technique to analyze the stability around a spherical body with a mass anomaly at its equator. Varying the parameters of the central object, we verify the existence of two distinct regions around the body, a chaotic inner region where particles are lost and a stable outer region. In the stable region, spin-orbit resonances are identified, and we obtain that periodic orbits in 1:1+p resonances are asymmetric. Modeling Chariklo as an object with a mass anomaly, we conclude that its rings are in the stable region, but not involved in the 1:3 spin-orbit resonance, as proposed in the literature. The results presented here aim to shed light on the processes involved in the formation of satellites and ring systems, as well as understanding their stability. We also tried to underline the symbiotic relationship between rings and satellites. The different methodologies employed in this thesis can be adapted to other systems in order to bring better knowledge about the origin and fate of other satellites and rings of the Solar System.